THE PROSPECTS FOR APPLICATION OF NEUTRON-FRAGMENT RADIOGRAPHY IN STUDY OF LOCAL DISTRIBUTION OF URANIUM IN THE BAIKAL SEDIMENTS FOR PALEOCLIMATIC RECONSTRUCTIONS - Zhmodik S.M.; Mironov A.G.; Nemirovskaya N.A. (My University, 1999)
Data on the local distribution of uranium throughout the bottom sediments of Lake Baikal (Akademichesky Ridge, VER-95-2, St 3BC, 53°113′12″N, 108°25′01″E) have been first obtained using neutron-fragment radiography. Uranium is present in the sediments in various forms: evenly dispersed, in clays and diatoms; microand macroinclusions in highly radioactive minerals (uranium concentrators); and evenly dispersed, at microsites, with its contents 10-50 times exceeding those in clays and diatoms. Relative and absolute concentrations of uranium can be reliably determined in virtually any mineral. The uranium distribution throughout the Baikal bottom sediments shows a regular character. Using (n,f)-radiography for studying the sediments provides new information necessary for paleoclimatic reconstructions.